Signs of deterioration in infants discharged home following congenital heart surgery in the first year of life: a qualitative study. Issue 10 (28th January 2016) - Tregay, Jenifer; Brown, Katherine L; Crowe, Sonya; Bull, Catherine; Knowles, Rachel L; Smith, Liz; Wray, Jo
Abstract : Aims: To describe the ways in which parents recognise and make decisions about their child's symptoms following discharge home after congenital heart interventions in the first year of life and their experiences of seeking help. Methods: This was a qualitative study involving semistructured interviews with parents. Twenty-one parents were recruited to the study. Parents all had a child who had congenital heart surgery in their first year of life between September 2009 and October 2013 at one of three UK cardiac centres; the children had either died or were readmitted as an emergency following initial discharge. Results: Some parents were unable to identify any early warning signs. Others described symptoms of deterioration including changes in feeding and appearance, respiratory distress and subtle behavioural changes that may not be routinely highlighted to parents at discharge. Several barriers to accessing prompt medical assistance were identified including parents feeling that their concerns were not taken seriously, long wait times and lack of protocols at A&E. Conclusions: Our study highlights behavioural symptoms as being a potentially underemphasised sign of deterioration and identifies a number of barriers to parents accessing support when they are concerned. It is important that parents are encouraged to seek advice at the earliest opportunity and that those health professionals at the front line have access to the information they need in order to respond in an appropriate and timely way. A role for home monitoring was also noted as potentially useful in identifying at risk children who appear clinically well.